Massa mediastinal em lactente - relato de caso - Thiago Rezende Silveira; Daniel Pinheiro Ferreira; Elina Tosta Oliveira; Danielle Paula de Oliveira Gonçalves; Eliene Machado de Freitas Félix; Adriana Cartafina Perez Bóscollo (Residência Pediátrica, 2024)
INTRODUCTION: Mediastinal Teratoma is a neoplasm originating from germ cells and comprises about 8-16% of tumors in this region. They are uncommon in children and equally incident among sexes. Commonly, diagnosis is made after birth due to the emergence of respiratory symptoms, often being incidental. It presents an excellent prognosis when completely resected, highlighting the vital importance of early suspicion and diagnosis through imaging exams. OBJECTIVE: To highlight the occurrence of mediastinal tumors in children with a history of recurrent pneumonia presenting atypically, emphasizing the importance of considering mediastinal tumors as a differential diagnosis to ensure appropriate investigation. CASE REPORT: A 7-month-old infant presented to the Emergency Department of a university hospital in the interior of Minas Gerais, Brazil, with symptoms of tachypnea, respiratory failure, and rejection of maternal breastfeeding. The patient had multiple previous diagnoses of pneumonia with no response to antibiotic therapy. Imaging exams during the investigation revealed a mediastinal mass in the anterior compartment with fatty components and areas of calcification. Left thoracotomy was performed at the 5th intercostal space, with complete resection of the teratoma. The patient had complete resolution of symptoms and was followed up until 13 years of age without recurrence. CONCLUSION: Mediastinal tumors are rare and increase infant morbidity and mortality. Suspecting and applying appropriate diagnostic methods and surgical procedures are essential for treatment and reducing harm to these patients, who often undergo unnecessary treatments before diagnosis.